P40 Video clinics versus standard face-to-face appointments for liver transplant patients in routine hospital care: a feasibility randomised controlled trial of myVideoClinic. (28th September 2020) - Jones, Janet; Damery, Sarah; Francischetto, Elaine O'Connell; Lilford, Richard; Jolly, Kate; Ferguson, James
Abstract : Introduction: There has recently been a rapid increase in the number of health and social care organisations offering remote consultations in order to minimise the spread of disease following the outbreak of COVID-19, but their effectiveness is unclear. The majority of studies focusing on remote consultations to date have evaluated telephone appointments. Although some studies have used video conferencing technology in the secondary care sector, the sample sizes have been small and they differ in their findings. This study evaluated the feasibility of implementing video clinics at a large hospital trust in the UK and assessed whether the intervention improved patient satisfaction compared to standard face-to-face appointments for liver transplant patients. Methods: Clinically stable liver transplant patients were randomised to video clinic appointments (intervention) or standard face-to-face appointments (usual care). The intervention group had routine follow-up appointments via secure video link. Participants were asked to complete post-appointment questionnaires over 12 months. The primary outcome was the difference in scores between baseline and study end by patient group for three domains of patient satisfaction using the Visit-Specific Satisfaction Instrument (VSQ-9). An embedded qualitative process evaluation used interviews to assess patient and staff experiences. Results: Fifty four patients were randomised: 29 to receive video clinics and 25 to usual care (recruitment rate 26.6%). Crossover from intervention to usual care was high (44.8%). 129 appointments were completed with 64% of questionnaires returned. Patient satisfaction (intention-to-treat analysis) increased in both intervention and usual care groups but the between-group difference was not significant after controlling for baseline scores. Video appointments were perceived to save patients time and money, and patients found video clinics to be less burdensome, with fewer negative impacts on their health. Technical problems with the software were common, however, the software is constantly evolving and as time goes on these types of problems should ease. Both clinicians and patients saw video clinic appointments as positive and beneficial. Discussion: The UK National Health Service is facing huge challenges with regards to staffing, budgets and space due to increasing patient numbers. Being innovative by using available technology to offer routine follow-up appointments via secure video link may help ease some of the burdens and free up clinic space for those patients who need to be seen face-to-face. This study outlines our experiences of using a remote video consultation system and the associated advantages and pitfalls.